Revitalisasi Seni Pertunjukan Tradisional Ketoprak Di Surakarta - Acmad Dipoyono (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2018)
Ketoprak is a local cultural heritage of Central Java (Surakarta) which is still popular with its people, even though its existence is up and down. The situation began to be marginalized into the original habitat, and enchanted to like a new aesthetic that causes ketoprak to shift its function and orientation. The development of Ketoprak in Surakarta is always dynamic, requires renewal to harmonize with the turmoil of people's lives, and the demands of the times. It needs the right creativity so that ketoprak as a local cultural heritage still has the spirit of Javanese tradition, as well as being alive and building the cultural identity of Surakarta and not distorting. This can be judged by how much the attention of the public, and officials / institutions related to the growth and development of ketoprak, as well as how consistent the actors in maintaining the conservation of traditional ketoprak art. Conservation is the preservation or protection that aims to protect the richness of art and culture, in this case the traditional art of ketoprak. Ketoprak must find an alternative solution so that its existence does not die. The most preventive and effective solution is the revitalization as well as the development of ketoprak for the regeneration of connoisseurs (spectators), as well as decoys (prospective successors) ketoprak art. The revitalization of ketoprak is one of the primordial steps to revive the interest of the younger generation in the traditional arts of ketoprak especially in Surakarta, so that ketoprak continues to exist as a local cultural heritage.Keywords: Ketoprak, Existence, Conservation, Revitalization